Qual será o legado da Copa do Mundo de Futebol de 2014 para o Brasil? - Marques, António Teixeira (Revista USP, 2013)
This paper seeks to analyze the legacy to be left by the World Cup 2014 after its closure. In the first part, we analyse the legacy of other major events, taking the Barcelona 1992 and Athens 2004 Olympic Games as references. In the second part, the article focuses on the analysis of documents that enable us to understand what activities and projects have been planned for the World Cup. Finally, in the last part we seek to assess how the documents that have been made public help to understand what the planned legacy of the World Cup is and its intended scope. This last aspect is analysed by taking the legacy of the London 2012 Olympic Games as a reference.